Konsep Pendidikan Akhlak “Mahmudah Dan Mazmumah” Bagi Guru Dan Murid Di Dalam Kitab Adab Al Alim Wa Al Muta’alim - Saputra, Doni; Rika Asmarani (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Education today is more concerned with material and scientific issues than ethics, morals and morals. Education should be able to touch various aspects of physical, spiritual, moral, ethical, psychological and physical. If not, education is just like teaching and nothing reaches students at all. So therefore, This Research is Motivated by the lack of morals possessed by generations of the nation as well as the lack of knowledge of morals, both mah easy (commendable) and mazmumah (despicable) morals. It is hoped that the existence of good moral education for teacher and student can make generations of the nation into a generation that is rahmatan lil alamin. From the emergence ot these problems there is a work of KH. Hasyim Asy’ari is the book of Adab Al Alim Wa Al Muta’alim , in which it offers various kinds of morals, both maheasy and mazmumah. The educational concepts described in this book are easy to understand and learn. The sources used as tendencies to write this book are the Al-Qur’an and Hadits, then packaged by KH. Hasyim Asy’ari became easier to understand for the students of knowledge ant those who teach it. This study uses the type of library research or library research. Where the sources used are primary data from book of Adab Al Alim Wa Al Muta’alim and secondary data from books, magazines, internet, newspapers, this study uses a deductive and inductive approach. This research concludes that the concept of moral education offered by KH. Hasyim Asy’ari, namely improving intentions, patience, qana’ah, by being like that it will produce commandable morals. And the morals that are presented are patient, sincere, zuhud, qana’ah, and others. While the moralsof the mazmumah are riya’, wanting to be respected, arrogant, envious, backbiting.